Circ_0022340 promotes colorectal cancer progression via HNRNPC/EBF1/SYT7 or miR-382-5p/ELK1 axis: Circ_0022340 promotes CRC - Liu, Zhaohui; Xu, Xiaoping; Chen, Dong; Zhang, Lei; Pan, Yuan; Liu, Daocheng; Shen, Minmin; Chen, Min (Cellular and Molecular Biology, 2022)
Circular RNAs (circRNAs) are characterized as a class of new noncoding RNAs and function in tumorigenesis of colorectal cancer (CRC). In our study, the molecule mechanism of circ_0022340 in CRC was investigated. For this aim, quantitative real-time polymerase chain reaction (RT-qPCR) was used to test gene expression in CRC cells. Cell function assays including 5-ethynyl-20-deoxyuridine (EdU), colony formation and transwell investigated the proliferation and migration capacity in CRC cells. Luciferase reporter and RNA immunoprecipitation (RIP)assays determined the interaction between circRNA, miRNA and mRNA. Western blot was used to test protein expression. An immunohistochemistry assay was used to assess the tumor growth in vivo. Results showed that Circ_0022340 was highly expressed in CRC cells. Circ_0022340 was formed from exon 5 to 6 of the synaptotagmin 7 (SYT7). Silencing of circ_0022340 suppressed CRC cell proliferation and migration. Functionally, circ_0022340 recruited heterogeneous nuclear ribonucleoprotein C (HNRNPC) to stabilize EBF1 mRNA and thereby activated SYT7. Moreover, circ_0022340 targeted miR-382-5p to up-regulate ETS transcription factor ELK1 (ELK1). It is concluded that Circ_0022340 promoted colorectal cancer progression via recruiting HNRNPC to stabilize EBF1 mRNA and thereby activated SYT7 or miR-382-5p/ELK1 axis, which might provide a novel target for CRC treatment.